Importance of early diagnosis of hearing loss in childhood: integrative literature review (Research, Society and Development, 2022)
Hearing impairment is characterized as any alteration or disturbance in hearing, modifying the ability to hear or discriminate sounds in a normal way, regardless of the cause, type or intensity. Being diagnosed according to the type and degree of loss, it can lead to delay in both speech and language, in intellectual and cognitive development. Thus, early diagnosis and intervention is very important, so that auditory development can be brought closer to normality as much as possible. The study aims to demonstrate the importance of early diagnosis of hearing loss in childhood. This is an integrative literature review, carried out in March and April 2022 through electronic searches in Google Scholar and SciELO databases. The search strategies made it possible to identify 1151 articles and in total 11 articles were selected because they met all the inclusion requirements. The results show that the early diagnosis of hearing loss in childhood with appropriate measures allows a better development in speech and language, as well as in the social, psychological and educational levels, thus favoring a more satisfactory prognosis. Therefore, the importance of an early diagnosis is evident so that an immediate professional intervention can occur, thus managing to minimize the changes and damage that hearing loss in childhood can cause.